Pernikahan “Pada Gelahang” - Windia, Wayan P. (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
Bali has changed. The world is no longer partially controlled by men but there are forms of marriage where both the bride and groom act as purusha (the power of patriarchy) or have the same rights and obligations between them. This qualitative study found that the number of bride and groom couples in Bali who choose the form of marriage "pada gelahang" (having the same rights and obligations), from year to year tends to increase. The background or main reason for choosing the form of the marriage is to continue the regeneration. There are three principles or attitudes of life that need to be held and respected so that the marriage achieves prosperity and happiness forever (find a forever happiness), namely paksa, lasia, and satya.